Embracing Thinking Diversity in Higher Education to Achieve a Lifelong Learning Culture - Luis Alberto Mejía-Manzano; Gabriela Sirkis; Juan-Carlos Rojas; Katherina Gallardo; Patricia Vázquez-Villegas; Claudia Camacho-Zuñiga; Jorge Membrillo-Hernández; Patricia Caratozzolo (MDPI AG, 2022)
The Fourth Industrial Revolution requires global, structural, and technological changes in all economic and production fields. The most apparent adaptation requirements fall on Generation Z individuals, who will have more and more responsibilities within organizations. The international reports of the World Economic Forum and the Organization for Economic Co-operation and Development indicate that this training will mainly require a strong development of thinking diversity and lifelong learning skills. This study presents an analysis of the education in these future skills that these individuals will need to work successfully throughout their careers, taking into account the evolution of conditions toward the changes expected in the following years. The methodology used in this research belongs to the field of futures studies. Through strategies in the field of foresight, various scenarios are proposed that involve the expected changes in the short, medium, and long term, both in higher education institutions and in industries and companies, to ensure the adaptation of Generation Z individuals to changes in work, workplace, and workforce. The findings show the strong influence that other skills and attitudes, such as self-esteem, self-efficacy, initiative, emotions, and motivation, have on the capacity for self-managed development throughout professional life.